Temperature-Dependent Network Modules of Soil Methanogenic Bacterial and Archaeal Communities - Liu, Pengfei; Klose, Melanie; Conrad, Ralf (Frontiers in Microbiology, 2019)
Temperature is an important factor regulating the production of the greenhouse gas CH4. Structure and function of the methanogenic microbial communities are often drastically different upon incubation at 45°C versus 25°C or 35°C, but are also different in different soils. However, the extent of taxonomic redundancy within each functional group and the existence of different temperature-dependent microbial community network modules are unknown. Therefore, we investigated paddy soils from Italy and the Philippines and a desert soil from Utah (United States), which all expressed CH4 production upon flooding and exhibited structural and functional differences upon incubation at three different temperatures. We continued incubation of the pre-incubated soils (Liu et al., 2018) by changing the temperature in a factorial manner. We determined composition, abundance and function of the methanogenic archaeal and bacterial communities using HiSeq Illumina sequencing, qPCR and analysis of activity and stable isotope fractionation, respectively. Heatmap analysis of operational taxonomic units (OTU) from the different incubations gave detailed insights into the community structures and their putative functions. Network analysis showed that the microbial communities in the different soils were all organized within modules distinct for the three incubation temperatures. The diversity of Bacteria and Archaea was always lower at 45°C than at 25 or 35°C. A shift from 45°C to lower temperatures did not recover archaeal diversity, but nevertheless resulted in the establishment of structures and functions that were largely typical for soil at moderate temperatures. At 25 and 35°C and after shifting to one of these temperatures, CH4 was always produced by a combination of acetoclastic and hydrogenotrophic methanogenesis being consistent with the presence of acetoclastic (Methanosarcinaceae, Methanotrichaceae) and hydrogenotrophic (Methanobacteriales, Methanocellales, Methanosarcinaceae) methanogens. At 45°C, however, or after shifting from moderate temperatures to 45°C, only the Philippines soil maintained such combination, while the other soils were devoid of acetoclastic methanogens and consumed acetate instead by syntrophic acetate oxidation coupled to hydrogenotrophic methanogenesis. Syntrophic acetate oxidation was apparently achieved by Thermoanaerobacteraceae, which were especially abundant in Italian paddy soil and Utah desert soil when incubated at 45°C. Other bacterial taxa were also differently abundant at 45°C versus moderate temperatures, as seen by the formation of specific network modules. However, the archaeal OTUs with putative function in acetoclastic or hydrogenotrophic methanogenesis as well as the bacterial OTUs were usually not identical across the different soils and incubation conditions, and if they were, they suggested the existence of mesophilic and thermophilic ecotypes within the same OTUs. Overall, methanogenic function was determined by the bacterial and/or archaeal community structures, which in turn were to quite some extent determined by the incubation temperature, albeit largely individually in each soil. There was quite some functional redundancy as seen by different taxonomic community structures in the different soils and at the different temperatures.